CXCL3 promotes liver cancer progression by modulating the tumor microenvironment via the PI3K/AKT/mTOR pathway - Yue Li; Tao Liu; Ziteng Cai; Chaonan Peng; Zhilei He; Lichun Liang; Bo Han; Ran Bi; Lei Liu; Weiqun Wang (PLoS ONE, 2025)
CXCL3, a member of the CXC chemokine family, has been increasingly implicated in the progression of various cancers, including hepatocellular carcinoma, due to its role in immune and inflammatory responses within the tumor microenvironment. This study aimed to investigate the expression and function of CXCL3 in liver cancer and to elucidate its underlying mechanisms. A combination of bioinformatics analysis, ELISA, RT-qPCR, immunohistochemistry, in vitro cell assays, and in vivo nude mouse models was employed to assess CXCL3 expression and function. The results showed that CXCL3 was significantly upregulated in hepatocellular carcinoma tissues and associated with reduced overall survival in patients. It promoted the proliferation, colony formation, and migration of liver cancer cells (Bel-7402, HepG2, and SMMC-7721) via exogenous, autocrine, and paracrine mechanisms, and recruited tumor-associated macrophages, neutrophils, and fibroblasts into the tumor microenvironment. Mechanistically, CXCL3 activated the PI3K/AKT/mTOR pathway by upregulating PI3K, p-PI3K, AKT, p-AKT, mTOR, and p-mTOR, while the mTOR inhibitor Torin 1 reversed these effects. Gene set enrichment analysis showed enrichment in immune-related pathways, including Toll-like receptor and chemokine signaling. In vivo, CXCL3 overexpression significantly promoted tumor growth in nude mice. These findings suggest CXCL3 facilitates liver cancer progression through tumor microenvironment modulation and PI3K/AKT/mTOR pathway activation.